A Robust Navigation Technique for Integration in the Guidance and Control of an Uninhabited Surface Vehicle. (3rd March 2015) - Annamalai, A.; Motwani, A.; Sharma, S.K.; Sutton, R.; Culverhouse, P.; Yang, C.
Abstract : This paper proposes the novel use of a weighted Interval Kalman Filter (wIKF) in a robust navigational approach for integration with the guidance and control systems of an uninhabited surface vehicle named Springer . The waypoint tracking capability of this technique is compared with that of one that uses a conventional Kalman Filter (KF) navigational design, when the model of the sensing equipment used by the filter is incorrect. In this case, the KF fails to predict correctly the vehicle's heading, which consequently impacts negatively on the performance of its integrated navigation, guidance and control (NGC). However, the use of a wIKF technique that is immune to this kind of erroneous modelling endows the integrated NGC system with better accuracy and efficiency in completing a mission.